Evidence for a new regional NW–SE fault and crustal structure in Tunisia derived from gravity data. (6th May 2015) - Arfaoui, Mohamed; Reid, Alan; Inoubli, Mohamed Hedi
ABSTRACT: A new Tunisian gravity map interpretation based on the Gaussian filtered residual anomaly, total horizontal gradient, and Moho discontinuity morphology established from gravity data exhibit a new regional northwest–southeast fault extending from Eastern Kairouan to Ghardimaou (Algeria–Tunisia Boundary). It presents a horizontal gradient maximum lineament that terminates the north–south Jurassic structures in the Kairouan plain. Further, this interpretation reveals other known fault systems and crustal structures in Tunisia. The new regional northwest–southeast fault constitutes with the north–south axis and Gafsa–Jefara faults the deepest faults coinciding with the Moho flexures, which had an important role in their initiation. They constitute the border intra‐continental crust faults of the Mesozoic rift. The newly recognized deep fault has critical implications for mineral and petroleum perspectives.